Advancements in electrode materials for aqueous ammonium-ion batteries - Zining Li; Liubing Dong (Energy Materials and Devices, 2025)
Aqueous ammonium-ion batteries (AAIBs) have emerged as a promising candidate for grid-scale energy storage owing to their intrinsic safety (e.g., dendrite-free and nonflammable), environmental friendliness, and potential for fast charge/discharge capability. Extensive research has been conducted in recent years to explore high-performance ammonium-ion storage materials and the associated electrochemistry to advance the commercialization of AAIBs. Therefore, it is necessary to review the progress in ammonium-ion storage materials and related electrochemical theories to guide further research on AAIBs. Herein, we systematically summarize the advanced electrode materials for AAIBs by introducing the physicochemical characteristics and ammonium-ion storage behaviors of various electrode materials, such as Prussian blue analogs, organic polymers, and metal oxides, discussing feasible material-design strategies to enhance their ammonium-ion storage performance, and outlining the future development prospects of AAIBs. This review aims to provide valuable insights into the design of advanced electrode materials for high-performance AAIBs.